Gas seepage laws based on dual porosity and dual permeability: Numerical simulation and coalbed methane extraction practice. Issue 4 (1st February 2021) - Xu, Chao; Qin, Liangliang; Wang, Kai; Sun, Haoshi; Cao, Mingyue
Abstract: Coalbed methane (CBM) is the very important unconventional energy resource. Enhancing extraction is the main method to improve the utilization of CBM and prevent coal mine gas disasters. To reveal the laws of gas migration during the underground gas extraction, the paper established the solid‐gas coupling model, regarding coal as the homogeneous elastic medium with dual pore‐fracture structure and dual permeability and considering the gas dynamic diffusion coefficient. Then, the regulations of gas migration in the in‐seam borehole were simulated by the COMSOL Multiphysics software and verified via the field trials of gas extraction. The results revealed that the permeability increased with time due to the coupling of matrix shrinkage and volume compression of coal, in which the matrix shrinkage played a leading role. The gas seepage velocity at the observation points can be divided into three stages: the rapid rise stage, the stable decline stage, and the stable and invariant stage. The gas extraction rate continued decreasing with time and finally tended to a fixed value. In the coal seam #4 of Zhongxing coal mine, the measured flow rates of three in‐seam drilling holes were in good agreement with the simulation results, which verified the correctness of the theoretical coupling model. Abstract : A solid‐gas coupling model of coal containing methane with dual porosity/dual permeability was established. The distribution of matrix gas pressure, fracture permeability, and seepage velocity were obtained. The dual‐porosity/dual‐permeability model was verified by experimental results of CBM extraction.